Epidemiology of the hepatitis C virus - Communicable Diseases Network Australia; New Zealand; Crofts, Nick; Thompson, Sandy; Kaldor, John (Communicable Diseases Intelligence, 2024)
Technical Report Series No. 3 ISBN 0642 393090 7 The availability since 1990 of commercial assays to test for infection with the hepatitis C virus (HCV) enabled investigation of its epidemiology to begin in earnest. Current serological assays do not distinguish between incident and old infections, or whether infections acquired have resolved or remain to cause ongoing liver damage. Measurement of markers in the serum does not necessarily reflect what is occurring in the liver. Moreover, the costs associated with tests such as quantitative polymerase chain reaction (PCR), genotyping and serotyping, in addition to the need to avoid repeated invasive liver biopsies, means that our knowledge at this early stage of investigation of the epidemic is imperfect. This report of the epidemiology of HCV summarises the state of knowledge to the end of 1998. The report is based upon extensive literature reviews of the world medical literature and the compilation of a research register that identifies Australian studies completed or in progress and the ideas which researchers and practitioners involved in HCV have identified as areas where information is deficient.